Pectins from dragon fruit (Hylocereus polyrhizus) peel - Nazaruddin, R.; Norazelina, S.M.I.; Norziah, M.H.; Zainudin, M. (Penerbit Universiti Kebangsaan Malaysia, 2011)
The extraction of pectin from a by-product of dragon fruit processing, was identified as an alternative source for commercial pectin. In this work, dried alcohol-insoluble residues (AIR) of dragon fruit peels were treated separately with ammonium oxalate/oxalic acid 0.25 %, pH 4.6, 85oC; HCl 0.03 M, pH 1.5, 85oC; and deionised water, 75oC. The pectin obtained from these methods were compared in term of yield, color, gelling characteristic and chemical structure. The highest yield for the extracted pectin from dragon fruit peels was 20.1 % (dry weight basis) by ammonium oxalate/oxalic acid extraction, contained 11.2 % moisture and 6.9 % ash. Extraction by deionised water yielded 15.4 % pectin, 11.3 % moisture and 11.6 % ash. Whereas, the acid extraction gave the lowest yield 15 %), 11.1 % moisture and 12 % ash. The amount of pectin from all extraction conditions were comparable to pectin obtained from commercial apple (12 %) or citrus (25 %). Gel hardness test was performed for gelling properties measurement. The Fourier Transform Infrared Spectroscopy (FTIR) was useful in the identifying dragon fruit pectins. Different conditions used in the extraction do not show a difference in the pectin structure. With a good recovery yield and gelling properties, ammonium oxalate-extracted dragon fruit pectin present good characteristics to be exploited industrially as food additive.